Natural mutations in key NLS amino acids regulate nucleoplasmic shuttling and replication efficiency in PRRSV - Zhu, Xianchang; Xia, Yang; Lei, Qian; Gan, Yu; Jiang, Shenghai; Huang, Lian; Wen, Qihu; Fu, Wei; Zhang, Bo; Zhang, Yi; Xie, Shanshan; Li, Jida (Frontiers in Microbiology, 2025)
Highly pathogenic porcine reproductive and respiratory syndrome virus (HP-PRRSV) is a mutant strain of the classic porcine reproductive and respiratory syndrome virus (PRRSV) characterized by high morbidity and mortality rates. Epidemiological analysis revealed a natural mutation and stable inheritance of amino acid 46 (41-PGKKNKK-47 mutated to 41-PGKKNRK-47) in the nuclear localization signal or sequence (NLS) region of the N protein of HP-PRRSV. In this study, we showed that the nucleoplasmic shuttling of the HP-PRRSV N protein was associated with a higher efficiency of viral replication than that of the classical PRRSV. The nuclear transporter receptors KPNB1, KPNA1, KPNA2, KPNA6, and KPNA7 were involved in the nuclear import of the N protein. Additionally, the mRNA expression levels of KPNB1 and KPNA1 differed between the two strains after infecting the Marc-145 cells with these strains. The viral replication efficiency also decreased when expression levels of KPNA1 and/or KPNB1 were lowered. Finally, protein binding simulation and kinetic assay showed that the mutation of key amino acid 46 in the NLS region altered the binding mode and kinetics of the N proteins to KPNA1 and KPNB1. This study elucidates, for the first time, the reasons for the enhanced nucleoplasmic shuttling and replication efficiency of HP-PRRSV from the perspective of protein entry into the nucleus. It also provides a foundational reference for the prevention and control of PRRSV.